GAMBARAN KARAKTERISTIK KEPRIBADIAN DAN NILAI GURU EFEKTIF YANG DISUKAI BERDASARKAN PERSPEKTIF SISWA SEKOLAH NEGERI DI JAKARTA TIMUR - ANNA ARMEINI RANGKUTI; HILMI ABDUL AZIS (Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2014)
This research aimed to look the picture of value and personality characteristic of effective teacher according to student from state school of East Jakarta perspective. This research use quantitative approach and descriptive method. Total sample of this research are 165 student with a accidental sampling technique. This instrument has been made based on the characteristic in UU of teacher 2005, research from Gao and Liu (2012), Mcber (2004), and Big Five personality trait. The result of this research found that good characters, drive to improve, patience, respectfulness, agreeability are the effective teacher’s value and personality characteristic.